Analisis Kemampuan Berpikir Kritis Matematis menggunakan Pendekatan Blended Learning pada Siswa Kelas VIIB Di SMP Negeri 6 Lembor - Laurensius Jangko; Timbul Yuwono (Prodi Pendidikan Matematika, Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2024)
The background to this research is based on observations of students at SMP Negeri 6 Lembor, East Nusa Tenggara, where mathematical critical thingking abilities were still low. Data collection techniques include test results, interviews, and documentation. This data collection used critical thingking ability tests and interviews with twenty students from class 7B, even during the semester of the 2021/2022 academic year. Data analysis techniques use data reduction, data presentation, and concluding students' critical thinking skills in solving mathematical problems using the Blended Learning approach. The results showed that students with critical thinking skills in the 'low' category were only able to fulfill one indicator and did not fulfill all of them because they had not been able to understand the meaning of the problem, formulate concepts, write solutions, and draw conclusions properly and correctly. Students with 'medium' critical thinking skills can meet 2 to 3 indicators because they can only choose the right solution strategy but are still wrong and make mistakes in their calculations. In contrast, students with 'high' critical thinking skills meet all ability indicators—critical thinking. Because students can choose a solution strategy and give reasons related to the chosen strategy wholly and correctly, it can be concluded that as many as 80% can think critically in the 'low' category, as much as 10% can think critically in the 'medium' category, and 10% can think critically in the 'high' category.